The Face of Prabowo Subianto as Elected Indonesia’s President on Al-Jazeera Arabic: A Roger Fowler’s Critical Discourse Analysis - Ulum, Muhammad Bachrul; Nisa’, Hanun Khiyarotun; Febrianto, Ahmad Fathon; Susi Khoidatul Sofia, (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Al-Jazeera Arabic is one of the Middle Eastern media outlets with a high intensity of reportage on Indonesia. This study aims to examine how Al-Jazeera Arabic reported the victory of Prabowo Subianto in the 2024 Indonesian presidential election. It employs Critical Discourse Analysis based on the model proposed by Roger Fowler et al. as an ideological framework to analyze the discourse surrounding Prabowo Subianto’s election as the eighth President of the Republic of Indonesia. From Fowler’s perspective, a media outlet’s stance toward an issue can be observed through its two outermost layers: lexical choice (diction) and syntactic construction (structure). Based on an analysis of four news reports on Prabowo Subianto as the president-elect, Al-Jazeera at the lexical level frequently employs the epithet “al-jinīrāl al-sābiq” (“the former general”), etc which functions as an affirmation of his past as an Indonesian National Armed Forces (TNI) general one marked by controversy and closely associated with alleged human rights violations in 1998. At the structural level, Al-Jazeera consistently affiliates Prabowo with Joko Widodo, portraying him variously as a rival, a subordinate, and as politically linked through his partnership with Widodo’s son as the vice-presidential running mate.